2021
DOI: 10.3389/fbioe.2021.807625
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ball Milling Time on the Isolation of Lignin in the Cell Wall of Different Biomass

Abstract: Ball milling technology is the classical technology to isolate representative lignin in the cell wall of biomass for further investigation. In this work, different ball milling times were carried out on hardwood (poplar sawdust), softwood (larch sawdust), and gramineous material (bamboo residues) to understand the optimum condition to isolate the representative milled wood lignin (MWL) in these different biomass species. Results showed that prolonging ball milling time from 3 to 7 h obviously increased the iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…When the grinding time was over 12 h, the extraction rate of ball-milled lignin was no longer significantly improved. Previous studies showed that the extraction rate of ballmilled lignin can be improved by moderately prolonging the milling time[38,39]. The results of this study are consistent with previous studies.…”
supporting
confidence: 92%
“…When the grinding time was over 12 h, the extraction rate of ball-milled lignin was no longer significantly improved. Previous studies showed that the extraction rate of ballmilled lignin can be improved by moderately prolonging the milling time[38,39]. The results of this study are consistent with previous studies.…”
supporting
confidence: 92%
“…Alternatively, mechanical treatment methods, such as ball milling, have been used to reduce the particle size of lignin and eventually affect structural/chemical properties. Ball milling has been mostly used to assist with lignin isolation from biomass [ 84 , 85 ]. In the present study, the pristine kraft lignin was ball milled (BMKL) to primarily decrease its particle size (as discussed below).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the previously reported results [ 23 ], a protocol based on the use of ChCl:LA2 as DES was adopted for the recovery of lignin from the selected nut shells. Before extraction, the latter were finely minced with the aid of a ball mill with the aim of improving the extraction yields by both increasing the surface area and cleaving glycosidic bonds and β-O-4 bonds of lignin components [ 38 , 39 , 40 , 41 ], also resulting in the liberation of phenolic hydroxyl groups and hence, boosting of the antioxidant properties. Subsequent extraction was performed at 120 °C for 24 h, allowing for the recovery lignins in the form of brown/black powders by simple precipitation, centrifugation, and lyophilization.…”
Section: Resultsmentioning
confidence: 99%